2013
DOI: 10.1007/s13595-013-0266-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of ophiostomatoid fungi associated with the large pine weevil, Hylobius abietis, and infested Scots pine seedlings in Poland

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…This study confirmed an earlier finding (Linnakoski et al. ; Jankowiak and Bilański ) that G. radiaticola is widely distributed on the European continent, especially in association with root‐feeding bark beetles. Leptographium procerum , L. lundbergii and L. truncatum were also isolated at relatively high frequencies from root‐infesting beetles in this study, and these fungi have been associated with a wide range of bark beetles in Europe (Kirisits ; Linnakoski et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study confirmed an earlier finding (Linnakoski et al. ; Jankowiak and Bilański ) that G. radiaticola is widely distributed on the European continent, especially in association with root‐feeding bark beetles. Leptographium procerum , L. lundbergii and L. truncatum were also isolated at relatively high frequencies from root‐infesting beetles in this study, and these fungi have been associated with a wide range of bark beetles in Europe (Kirisits ; Linnakoski et al.…”
Section: Discussionsupporting
confidence: 92%
“…). The presence of G. radiaticola in Europe has also been recently recorded in association with H. abietis in Poland (Jankowiak and Bilański ). This study confirmed an earlier finding (Linnakoski et al.…”
Section: Discussionmentioning
confidence: 74%
“…Spread of the fungus may be aided further by adults being able to recognize trees that have been treated with insecticides and moving onto other trees after initial feeding, thus increasing encounter rates (Rose et al , ). Many insects facilitate the dissemination and infection of pathogenic fungi (Lévieux et al , ; Whitehill et al , ; Jankowiak & Bilański, , ), particularly via wounds on host plants (Palmer, ; Feci et al , ). Some insects have previously been associated with the transfer of D. sapinea , such as bark beetles ( Ips spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Pine weevils of the genus Pissodes are important pests on young pines in the Northeast zone, being widely distributed in the Baltic countries, Poland, Ukraine, Russia, and Finland. The most common species are P. castaneus, P. pini, and P. piniphilus [94,166,174]. Pissodes castaneus is one of the most dangerous pests of P. sylvestris plantations and natural regenerations in the Baltic region.…”
Section: Northeast Agro-climatic Zonementioning
confidence: 99%
“…Nannf. to P. sylvestris seedlings [174]. Its abundance, frequency as a damaging agent on pines, and recurrent association with pathogenic fungi increase the risk of it becoming associated with F. circinatum.…”
Section: Northeast Agro-climatic Zonementioning
confidence: 99%